The effects of early life trauma on the neurochemistry and behaviour of the adult rat - Uys, Joachim De Klerk (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Biomedical Sciences. Medical Physiology))--University of Stellenbosch, 2006.